Relasi Makna Dalam Bahasa Arab Dan Implikasinya Terhadap Pemahaman Kontekstual - Salsabila, Intan Nadia; Fithriyana, Fadlilatul (Mahira: Journal of Arabic Studies & Teaching, 2025)
Arabic semantics presents complex relationships, particularly through musytarak lafzi (lexical polysemy), mudhad (auto-antonyms), and ambiguity. These phenomena represent types of meaning relations that can significantly influence text interpretation when not approached contextually. This article aims to examine these three semantic features within Arabic linguistics and explore their implications for contextual understanding, especially in classical and religious texts. Using a qualitative, descriptive method, the study analyzes lexical examples from the Qur’an, hadits, and Arabic literary works. The findings show that musytarak lafzi in words such as ‘ʿayn’ (which may mean eye, essence, or spring) and mudhad in words like ‘zann’ (which can indicate certainty or doubt) often become major sources of ambiguity, potentially leading to misinterpretation if readers lack contextual awareness. Therefore, a deep understanding of these semantic relations is essential to achieve accurate comprehension of Arabic texts. This study concludes that contextual interpretation plays a vital role in clarifying lexical ambiguity rooted in Arabic’s semantic structures, thereby contributing to both linguistic analysis and the pedagogical development of Arabic language teaching.